Rearrangement and amplification of c-abl sequences in the human chronic myelogenous leukemia cell line K-562. - Collins, S J (1983)
Structural rearrangements of specific cellular sequences (c-onc genes) homologous to acute transforming retrovirus oncogenes (v-onc genes) have been recently described in various malignancies. Here we show that human cellular sequences (c-abl) homologous to the transforming sequences of the mouse Abelson leukemia virus (v-abl) are amplified some 4- to 8-fold in K-562, a Philadelphia chromosome-positive cell line derived from a patient with chronic myelogenous leukemia in blast crisis. Restriction analysis of K-562 and other human DNA samples reveals a significant rearrangements of the c-abl sequences in this cell line. In addition, investigation of v-abl-related cytoplasmic RNA reveals relatively high levels of these sequences in K-562 compared to other normal and leukemia cells. We have also observed that lambda light chain constant region immunoglobulin genes are amplified in K-562, whereas kappa light chain sequences exhibit no amplification. These results are discussed within the context of the possibility that these Philadelphia chromosome-positive cells exhibit a reciprocal translocation involving chromosome 9 (containing c-abl) and chromosome 22 (containing the lambda light chain genes).